Sports ethics for sports management professionals - Champion, Walter T. Jr., Esq. 1950-; Karcher, Richard T. Esq.; Ruddell, Lawrence S. PhD. (Burlington, MA Jones & Bartlett Learning, 2020)
Sports management professionals are confronted with many ethical decisions during their careers, and it's essential that they be equipped to make an informed decision when faced with a difficult situation. The goal of Sports Ethics for Sports Management Professionals, second edition is to provide professionals with the tools necessary to tackle these kinds of situations. The second edition presents several ethical models that sports management professionals can apply as a guide to making ethical decisions. it also considers areas significant within sports ethics, including race and discrimination, gender equity, privacy, violence, and drug use and drug testing. Sports Ethics for Sports Management Professionals contains numerous case studies that allow students to apply the ethical decision-making process to sports-related ethical disputes, as well as cases showing how ethical situations are addressed by the legal system in the United States
Ethical concepts in sports -- Sportsmanship, gamesmanship, and cheating -- Gambling in sports and society -- Ethical issues involving coaches -- Ethical considerations involving parents and fans -- Violence in sports -- The ethical use of drug use and testing -- Ethical considerations of race in sports -- Ethical duties of sports agents -- Gender discrimination and title ix -- Ethical considerations in sports media -- Commercialization of college sports
Revised edition of: Sports ethics for sports management professionals / Patrick K. Thornton, Walter T. Champion, Jr., Lawrence S. Ruddell.
Includes bibliographical references and indexes
Keywords: Sports administration; Sports -- Moral and ethical aspects